Slides to Philosophy 167: Class 10 -- Huygens and the Beginnings of Rational Mechanics -- Part 8. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 10, Part 8.